Troponin I levels in extracorporeal membrane oxygenation following congenital heart surgery - Rüffer, André; Münch, Frank; Potapov, Sergej; Purbojo, Ariawan; Toka, Okan; Dodge-Khatami, Ali; Dittrich, Sven; Cesnjevar, Robert (World Journal for Pediatric and Congenital Heart Surgery, 2014)
Correlating postcardiotomy extracorporeal membrane oxygenation (ECMO) troponin I (TnI) levels and outcomes.Between January 2006 and August 2010, 34 patients needed postcardiotomy ECMO for low cardiac output. Bailout ECMO was required either after unsuccessful weaning from bypass (n = 17, 50%), postoperatively from prolonged hemodynamic failure (n = 8, 23.5%), or following resuscitation (n = 9, 26.5%). The TnI levels were measured following surgery or resuscitation during 10 days and compared between survivors (group I) and non-survivors (group II).Median support duration was seven days (range: 0-31). Surgery involving hypoplastic aortic arch repair (Norwood palliation; n = 7, 20.6%, or biventricular repair; n = 11, 32.4%) led to most ECMO runs. Successful weaning from ECMO and hospital survival were 76.5% and 50%, respectively. In group I, peak TnI levels were reached by 24 hours postoperatively, comparable to levels in group II (36 ± 34 vs 49 ± 38 ng/mL; P = .98). However, in group II, TnI levels formed a plateau by the second postoperative day, whereas group I showed a steep decline in TnI levels, suggesting myocardial recovery (P = .028). All patients (n = 4) who reached or maintained peak TnI levels at 48 hours died. On days 8, 9 and 10, TnI levels were significantly higher in group II (P = .024, .019, and .013, respectively).Postcardiotomy ECMO was most commonly required after aortic arch repair. In the absence of ongoing myocardial insult due to ECMO hardware issues, coronary insufficiency or residual lesions, plateau TnI levels at 48 hours may seem to indicate an unfavorable outcome due to irreversible myocardial damage.
EVALuna2:25107